Plant Connections Member's Manual - Janice Easton; Deborah J. Glauer (EDIS)
The Kids Growing with Plant Connections Youth Workbook (4H194/4H PSM 11) is aimed at educating youth about the basics of horticulture. Youth will be exposed to information on plants and the plant kingdom. Lessons include: What Is a Plant?–Why Are Plants Important?–What Makes Plants Grow?–How to Grow Plants–How to Select and Handle Plants. The Plant Connections Leader’s Guide (4H192/4H PSL 21) is used in conjunction with this youth workbook. This revised 25-page workbook was written by Janice Easton and Deborah J. Glauer, and published by the UF Department of 4-H Youth Development, January 2015.